Pain sensitivity and athletic performance - Zeller, L.; Shimoni, N.; Vodonos, A.; Sagy, I.; Barski, L.; Buskila, D. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The objective of the study is to determine whether higher pain thresholds are associated with better performance in long-distance runners. METHODS: Seventy participants, divided into groups of fast and non-fast runners according to peak results in a 10km run. Main Outcome Measures, Cold pressor test. RESULTS: Of the 70 participants, 28 were in the fastest group (less than 39 minutes in a 10km run) and 42 in the non-fast group. The faster group was characterized with older age (34.0±8.5 vs. 29.5±5.7, P=0.01), greater mean weekly running time (5.5 [0-17]) vs. 2 [0-10], P<0.001), and more years of running (10 [1.5-34.0] vs. 7 [0-20, P=0.05]). In a multivariable analysis longer cold pressor time was associated with faster 10Km run (OR 1.01, 95% CI 1.00-1.01). CONCLUSIONS: It seems that higher pain thresholds play an important role in the superior ability of long distance runners.